Increasing tropical cyclone intensity and potential intensity in the subtropical Atlantic around Bermuda from an ocean heat content perspective 1955–2019. (2nd March 2021) - Hallam, Samantha; Guishard, Mark; Josey, Simon A; Hyder, Pat; Hirschi, Joel
Abstract: We investigate tropical cyclone (TC) activity and intensity within a 100 km radius of Bermuda between 1955 and 2019. The results show a more easterly genesis over time and significant increasing trends in TC intensity (maximum wind speed (Vmax)) with a decadal Vmax median value increase of 30 kts from 33 to 63 kts ( r = 0.94, p = 0.02), together with significant increasing August, September, October sea surface temperature (SST) of 1.1 °C (0.17 °C per decade) r = 0.4 ( p < 0.01) and increasing average ocean temperature between 0.5 °C and 0.7 °C (0.08 °C–0.1 °C per decade) r = 0.3( p < 0.01) in the depth range 0–300 m. The strongest correlation is found between TC intensity and ocean temperature averaged through the top 50 m ocean layer ( T 50 m ‾ ) r = 0.37 ( p < 0.01). We show how TC potential intensity (PI) estimates are closer to actual intensity by using T 50 m ‾ as opposed to SST using the Hydrostation S time-series. We modify the widely used SST PI index by using T 50 m ‾ to provide a closer estimate of the observed minimum sea level pressure (MSLP), and associated Vmax than by using SST, creating a T 50 m ‾ PI ( T 50 m ‾ _PI) index. The average MSLP difference is reduced by 12 mb and proportional ( r = 0.74, p < 0.01) to the SST/ T 50 m ‾ temperature difference. We also suggest the index could be used over a wider area of the subtropical/tropical Atlantic where there is a shallow mixed layer depth.